Kinematics Analysis of the Circuit Board Gripper Mechanism - Wan Qiuli; Ji Houhong; Liu Yu (Jixie chuandong)
Designing an excellent end effector is effective to improve a robot's performance. The kinematics analysis of a circuit board gripper mechanism used in ABB IRB1200 robot is discussed. The working principle of the circuit board gripper mechanism is analyzed; the displacement, velocity and acceleration of the gripper mechanism are solved with analytical methods; the mechanism is analyzed with the theory of kinematic influence coefficient. The motion parameter curve is drawn with the Matlab software in order to verify the analysis results obtained by the analytical method. The kinematics simulation analysis of the mechanism is carried out after defining the connecting rod and the kinematic pair, and giving the motion control function of the driving part, etc. in the UG software; the corresponding motion parameter curve is outputted at the same time. It can be shown that the motion analyses are completely consistent under both the Matlab and the UG environments; strong theoretical support for practical application of the gripper is provided by this motion analysis. This design is effective, which is demonstrated by good operating status of the assembled circuit board gripper mechanism.